Proses Pra-Peradilan dalam Tindak Pidana Terorisme : Pelanggaran Hak Asasi Manusia Terhadap Upaya Paksa Yang Dilakukan Oleh Kepolisian - Biruni, Zahid Ghulam; Miskiah, Siti (Jurnal De Jure Muhammadiyah Cirebon, 2025)
This research aims to analyze the Pre-Trial process in handling terrorism criminal acts in Indonesia, highlighting the implications of potential human rights (HAM) violations arising from coercive measures by the police. This study examines the crucial role of Pre-Trial as a judicial oversight instrument of police actions during the investigation, identifying potential human rights violations such as arbitrary arrests and detentions, torture, and restrictions on the rights of suspects. Furthermore, this research explores the challenges of effective Pre-Trial implementation in the context of the urgency of counter-terrorism and public pressure, as well as formulating policy recommendations to strengthen oversight, guarantee the protection of suspects' human rights, and create a balance between effective law enforcement and the state's obligation to uphold the rule of law. Keywords: Pre-Trial, Terrorism, Human Rights, Law Enforcement.